The Role Of Dream In The Regulation Of Formalin Induced Pain In Rapid Eye Movement (REM) Sleep Deprived Rats - Siran, Rosfaiizah (2011)
Rapid eye movement (REM) sleep deprivation has been shown to decrease pain threshold after various pain stimuli. Down regulatory antagonist modulator (DREAM) is a transcriptional repressor of prodynorphin gene. This study evaluates the effect on DREAM in relation to REM sleep deprivation, formalin induced pain or combination of both; and its relationship to the formalin induced pain behavioural responses. Male Sprague Dawley rats (250-300 g) were divided into four major treatments; free moving control (n=36), REM sleep deprivation (n=36), tank control (n=36) and sleep recovery (n=36). REM sleep deprivation was elicited for 72 hours using the inverted flower pot technique. Each group was further divided into two groups which consisted of rats that were either not or subjected to 2.5% formalin subcutaneous injection. Food consumption and body weight gain were measured before and after the treatments. The formalin induced pain behavioural responses were recorded for one hour for rats that subjected to formalin injection. The ventrobasal thalamic complex of brain (VB) were removed from each group for immunohistochemistry (n=6), Western blot (n=6) and real-time PCR analysis (n=6) separately. The ‘inverted flower’ pot technique was confirmed to induce REM sleep deprivation in the REM sleep deprived and sleep recovered rats by the classic pattern of hyperphagia with converse loss of body weight. There is a marked hypoalgesia demonstrated in the second phase of formalin induced pain in the REM sleep deprived rats. REM sleep deprivation per se did induce morphological change and reduced the number of DREAM positive neurons (DPN) bilaterally.